Antidiabetic Activity of Leaves Ethanol Extract Chromolaena odorata (L.) R.M. King on Induced Male Mice with Alloxan Monohydrate - Marianne Marianne; Dwi Lestari; Elin Yulinah Sukandar; Neng Fisheri Kurniati; Rosnani Nasution (Jurnal Natural, 2014)
Chromolaena odorata or Tekelan has been used traditionally to cope with diabetes mellitus, but the scientific evidence as antidiabetic agent has not been previously reported. Therefore, it is necessary to test the antidiabetic activity using ethanol extract of the tekelan leaves in male mice induced by alloxan. Mice were induced intravenously by alloxan dose of 55 mg/kg bw. After 7 days, mice were diabetic ( KGD 200 mg/dL ) and were grouped into 6 groups: negative control group (only treated with CMC - Na) , positive control group (glibenclamide 0.45 mg/kg bw) and the 4 other groups were given ethanol extract of Tekelan leaves at doses of 5 , 25 , 125 and 250 mg/kg bw. Dosage administered for 28 days and blood glucose levels was checked every 7 days using a glucotest. Data were analyzed by one-way analysis of variation at 95% confidence level. Ethanol extract of tekelan’s leaves  at doses of 5 , 25 , 125 and 250 mg/kg bw can lower blood levels  from day 7 to day 28 and was significantly different compared to the negative control group ( p 0.05). Ethanol extract of tekelan’s leaves at doses of 5 , 25 , 125 and 250 mg/kg bw showed antidiabetic activity in alloxan-induced mice.